Determination of streptomycin and doxycycline using LC/MS towards an effective treatment against an experimental Brucella abortus infection in mice - Sancho, Eugenia (2022)
The authors would like to thank the Costa Rican National Council of Provosts who partially funded this research (grant FEES-CONARE, 803- C2-651/SIA0492-21)(https://www.conare.ac.cr) and fellowship support for Eugenia Sancho from the Master’s Programme in Microbiology, University of Costa Rica.